Intraoperative Ultrasound in the Treatment of Breast Cancer - Eggemann, H.; Ignatov, T.; Beni, A.; Costa, S. D.; Ortmann, O.; Ignatov, A. (Geburtshilfe und Frauenheilkunde, 2013)
Purpose: The aim of this study was to investigate the value of intraoperative ultrasound in breast-conserving operations and to compare it with standard procedures. Methods: For this purpose 307 women with palpable breast cancers and 116 patients with non-palpable breast cancers were compared retrospectively. In the group with palpable breast cancers 177 patients were treated by US-guided operations and 130 patients underwent palpation-guided breast-conserving operations. As primary outcomes, the resection margins and the rate of re-operations were evaluated. Results: With regard to disease-free resection margins, intraoperative ultrasound was significantly superior to palpation alone. In the group of patients in whom the tumours were extirpated with the help of palpation, R1 resections were observed almost twice as often (16.9 %) as in the US-guided group (8.5 %). In the group with non-palpable breast cancers, intraoperative ultrasound was employed in 61 patients. As a control, 43 cases were evaluated in whom the breast-conserving operation was performed after wire marking. In this group US-guided tumour removal proved to be superior to that after wire marking for tumours that did not exhibit any intraductal components. Otherwise the redo resection rate was reduced by use of ultrasound. Furthermore, the surgeon was able by means of intraoperative ultrasound to identify “problematic” margins and to excise them in the same sitting. Conclusions: The US-guided, breast-conserving operations led to a lower rate of R1 resections and redo operations in comparison to operations with palpation alone or those after wire marking.
Keywords: breast cancer; ultrasound; gynaecology